Pravnoformalni okvir boja zoper diskriminacijo na etnični osnovi - Brezigar, Sara (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2009)
Legal framework aimed at fighting discrimination on ethnic grounds. The paper provides an overview and comparison of the legal framework aimed at fighting discrimination on ethnic grounds in a selection of EU member states. On the basis of the provisions of the Council Directive 2000/43/EC implementing the Principle of Equal Treatment Between Persons Irrespective of Racial or Ethnic Origin, the author compares the situation of non-EU citizens in Slovenia, the Czech Republic, Lituania, Greece, the Netherlands, Finland, Portugal and Germany. The article explores, to what extent the above mentioned states comply with the provisions of the Directive, or even exceed them, and seeks for answers to the following questions: how do selected member states define discrimination, which bodies have they established for the promotion of equality, what kind of procedures have they put in place to deal with cases of alleged discrimination and what are their difficulties in the implementation on antidiscrimination law? The analysis has shown that the antidiscrimination legal framework is, in general, adequate in Finland, Germany, the Netherlands, Portugal, Slovenia and to a certain extent also in Greece.
Keywords: European Union; Evropska Unija; tujci; diskriminacija; preprečevanje; zakonodaja; human rights; človekove pravice; direktive